PENGARUH MODEL PEMBELAJARAN STAD (STUDENT TEAM ACHIEVEMENT DIVISION) TERHADAP HASIL BELAJAR SISWA PADA SUBTEMA 1 KELAS IV UPTD SD NEGERI 122350 KOTA PEMATANG SIANTAR - Situmorang, Dea Cristivani; Tambunan, Janwar; Simanjuntak, Melvin (Universitas Katolik Santo Thomas Medan, 2024)
Based on the research results, it was found that the use of the STAD (Student Team Achievement Division) learning model had an influence in improving student learning outcomes in subtheme 1 class IV UPTD SD Negeri 122350 Pematang Siantar City FY 2022/2023. Research data supports this conclusion. Researchers found that the pretest score of class IV students was 43.43 and their posttest score was 76.93. The hypothesis in the paired sample t test shows that the sig (2-tailed) value is smaller than 0.05 (0.00 < 0.05) and tcount > ttable (13.587 > 2.056), indicating that the STAD (Student Team Achievement Division) learning model influence on student learning outcomes in sub-theme 1 theme 2 class IV UPTD SD Negeri 122350 Pematang Siantar City T.A 2022/2023.